Experimental and theoretical studies of benzothiazole derivatives as corrosion inhibitors for carbon steel in 1 M HCl. (November 2016) - Hu, Zhiyong; Meng, Yanbin; Ma, Xuemei; Zhu, Hailin; Li, Jun; Li, Chao; Cao, Duanlin
Highlights: Benzothiazole derivatives BTC6 T and BTC8 T were synthesized. Their corrosion inhibiting effect against steel in a 1 M HCl solution was studied. EIS, potentiodynamic polarization, and weight loss methods were used for analysis. These inhibitors were adsorbed onto surfaces by both physical and chemical means. Both inhibitors offered enhanced stability and inhibition efficiencies. Abstract: Two benzothiazole derivatives, namely 2 - ( n -hexylamino)-4-(3′- N, N -dimethylamino-propyl)amino-6-(benzothiazol-2-yl)thio-1, 3, 5- s -triazine (BTC6 T) and 2-( n -octylamino)-4-(3′- N, N -dimethylamino-propyl)amino-6-(benzothiazol-2-yl)thio-1, 3, 5- s -triazine (BTC8 T), were synthesized to study their corrosion inhibiting effect against steel in a 1 M HCl solution. The corrosion inhibition efficiency was measured using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, and weight loss methods. Both inhibitors offered extra stability and higher inhibition efficiencies again steel corrosion than previously reported benzothiazole family inhibitors. These inhibitors can be adsorbed onto surfaces by both physical and chemical means. Finally, quantum chemical parameters were calculated using the density functional theory method (DFT) and the correlation between the theoretical and experimental results are discussed.